2009
DOI: 10.2337/db09-0277
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Is a Novel Adipocyte-Derived Factor Inducing Insulin Resistance in Primary Human Skeletal Muscle Cells

Abstract: OBJECTIVEChemerin is an adipokine that affects adipogenesis and glucose homeostasis in adipocytes and increases with BMI in humans. This study was aimed at investigating the regulation of chemerin release and its effects on glucose metabolism in skeletal muscle cells.RESEARCH DESIGN AND METHODSHuman skeletal muscle cells were treated with chemerin to study insulin signaling, glucose uptake, and activation of stress kinases. The release of chemerin was analyzed from in vitro differentiated human adipocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
279
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(297 citation statements)
references
References 47 publications
14
279
0
4
Order By: Relevance
“…metabolic diseases. Several recent studies have demonstrated that circulating chemerin levels are elevated in both obese humans and obese/diabetic experimental animals and are positively correlated with various aspects of metabolic syndrome (Bozaoglu et al, 2007;Sell et al, 2009). The administration of exogenous chemerin to obese/diabetic (but not normoglycemic) mice resulted in exacerbated glucose intolerance, lower serum insulin levels, and decreased tissue glucose uptake .…”
Section: Discussionmentioning
confidence: 99%
“…metabolic diseases. Several recent studies have demonstrated that circulating chemerin levels are elevated in both obese humans and obese/diabetic experimental animals and are positively correlated with various aspects of metabolic syndrome (Bozaoglu et al, 2007;Sell et al, 2009). The administration of exogenous chemerin to obese/diabetic (but not normoglycemic) mice resulted in exacerbated glucose intolerance, lower serum insulin levels, and decreased tissue glucose uptake .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PRAS40 (also known as AKT1S1) was silenced in hSkMC and the effects on insulin action were determined. In addition, we examined whether the chemokines chemerin and monocyte chemotactic protein 1 (MCP-1), which have been implicated in the induction of insulin resistance in hSkMC [25,26], exert an additive effect in hSKMC in which PRAS40 was silenced.…”
Section: Introductionmentioning
confidence: 99%
“…Increased serum levels of chemerin have been associated with chronic inflammatory diseases (19,20), coronary artery disease (21), the metabolic syndrome, and obesity (22). There is indication that high chemerin production in obese adipose tissue (23) might contribute to the increased infiltration of macrophages observed in obese adipose tissue leading to low-level inflammation (24).…”
mentioning
confidence: 99%